2018
DOI: 10.1055/s-0038-1676813
|View full text |Cite
|
Sign up to set email alerts
|

Use of Targeted High-Throughput Sequencing for Genetic Classification of Patients with Bleeding Diathesis and Suspected Platelet Disorder

Abstract: Inherited platelet disorders (IPD) form a rare and heterogeneous disease entity that is present in about 8% of patients with non-acquired bleeding diathesis. Identification of the defective cellular pathway is an important criterion for stratifying the patient's individual risk profile and for choosing personalized therapeutic options. While costs of high-throughput sequencing technologies have rapidly declined over the last decade, molecular genetic diagnosis of bleeding and platelet disorders is getting more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 51 publications
0
16
0
Order By: Relevance
“…However, over the past decade, high‐throughput sequencing has become the primary means of identifying disease‐causing genetic variants . Different diagnostic gene panel tests for BTPD have been developed using targeted or exome sequencing . Interestingly, when comparing the gene content of these different genetic panel tests, significant differences were observed.…”
Section: Introductionmentioning
confidence: 99%
“…However, over the past decade, high‐throughput sequencing has become the primary means of identifying disease‐causing genetic variants . Different diagnostic gene panel tests for BTPD have been developed using targeted or exome sequencing . Interestingly, when comparing the gene content of these different genetic panel tests, significant differences were observed.…”
Section: Introductionmentioning
confidence: 99%
“…Different HTS studies for diagnostics of BPD have been published but for this review, we have only focussed on the studies that have used the guidelines for variant classification as formulated by the American College of Medical Genetics (ACMG) in 2015 [10]. Figure 2 provides an overview of the diagnostic rates obtained in these studies that however differ in terms of used HTS methods (TS or WES), studied pathologies (platelet disorders, coagulation disorders and bleeding of unknown etiology) and the number of genes and patients included [11][12][13][14][15][16][17][18][19][20][21]. In addition, these studies have used different inclusion criteria ranging from the selection of only patients with a known or suspected etiology (studies with typically high diagnostic rates) to patients with bleeding of unknown etiology and normal laboratory parameters (studies with very low diagnostic rates).…”
Section: Hts Technologies Used For Bpd Diagnosticsmentioning
confidence: 99%
“…Other HTS studies have also reported variants in more than one gene but without further specifications if these had a clinical impact for the patient or family [11,[14][15][16][17][18]20]. Such examples of mostly digenic inheritance have recently also been documented in case reports.…”
Section: Accepted Articlementioning
confidence: 99%
“…The spread of next-generation sequencing (NGS) greatly contributed to the unraveling of the genetic basis of several forms of IPD, and thus immediately became a significant diagnostic tool in the field. Using a small amount of blood with minor risk of pre-analytical artifacts, it can provide patients with a highly accurate diagnosis [4][5][6][7][66][67][68][69][70][71][72]. As it becomes cheaper to perform, it is not inconceivable that NGS could become the standard above other diagnostic techniques.…”
Section: Current Diagnostic Tools For Ipdsmentioning
confidence: 99%